Tingkat Kecemasan Ibu Hamil Trimester I dan Munculnya Mual dan Muntah Kehamilan - Fitriyani Pulungan (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Nausea and vomiting in pregnancy are common symptoms in 60-80% of primigravida. The purpose of this study was to analyze the relationship between the level of anxiety of pregnant women in the first trimester with the appearance of nausea and vomiting during pregnancy. The design of this study was cross-sectional. Respondents were 33 first trimester pregnant women at the Tanjung Pratama Clinic and Rina BPM Medan during the period March to June 2017, selected by purposive sampling. Data were collected through filling out questionnaires and medical records, then analyzed using the Chi-square test. The results showed that the majority of pregnant women experienced moderate levels of anxiety (54.5%) and experienced nausea and vomiting during pregnancy (72.7%). The results of hypothesis testing showed p-value = 0.000, so it was concluded that there was a significant relationship between the anxiety level of first trimester pregnant women and nausea and vomiting during pregnancy. Keywords: first trimester of pregnancy; nausea and vomittng; anxiety ABSTRAK Mual dan muntah dalam kehamilan adalah gejala yang sering terjadi pada 60-80% primigravida. Tujuan penelitian ini adalah untuk menganalisis hubungan antara tingkat kecemasan ibu hamil Trimester I dengan munculnya mual dan muntah selama kehamilan. Rancangan penelitian ini adalah cross-sectional.  Responden adalah 33 ibu hamil trimester I di Klinik Pratama Tanjung dan BPM Rina Medan selama periode Maret sampai Juni 2017, yang dipilih dengan teknik purposive sampling Data dikumpulkanmelalui pengisian kuesioner dan rekam medik, lalu dianalisis menggunakan uji Chi-square. Hasil penelitian menunjukkan bahwa mayoritas ibu hamil mengalami tingkat kecemasan sedang (54,5%) dan mengalami mual dan muntah selama kehamilan (72,7%). Hasil pengujian hipotesis menunjukkan p-value = 0,000, sehingga disimpulkan bahwa bahwa ada hubungan yang bermakna antara tingkat kecemasan ibu hamil trimester I dengan mual dan muntah selama kehamilan.Kata kunci: kehamilan trimester I; mual dan muntah; kecemasan